Virtual learning styles: does gender matter? - Goulão, Fátima (2013)
Background: Online education has its particularities, challenges and ways to face the pedagogical relationship (students/ professor/ context) associated with that. The ubiquity that the virtual space provides allows greater flexibility of time and space. This flexibility can be reflected not only in access to knowledge, but also, in the way of structuring the training and in possibility to means and methodologies best suited to the needs and ways to students reach the knowledge (learning styles). Purpose of Study: Our goal were: a) to identify students’ profiles that use the virtual space in the online context and, b) to verify if there were differences in those profiles, in terms of gender. Research Methods: Data collection was made through a questionnaire composed of 3 parts. a) identification of the sample; b) questions to characterize the use made of the Internet; c) questionnaire of Virtual Space Style. The questionnaire indicates to 4 different styles. A total of 100 students participated in the survey. 27% are males and 73% are females. The average age is 32 years old. Findings: Our results point out to the predominance of one of the styles – type A -, called participatory use style in virtual space. We found significant differences between genders. Conclusions: Knowing virtual learning space users’ profile is very relevant to help us to understand the learning processes in these contexts. Furthermore, this knowledge provides us with the information required to structure the pedagogic context and the appropriateness of teaching methodologies.